THE IMPACT OF EXCHANGE RATE VOLATILITY ON FOREIGN DIRECT INVESTMENT: ARDL TESTING BOUND - Hamida, Arafet (International Journal of Islamic Business & Management, 2024)
Promoting sustainable development is one of the main objectives in emerging nations. In actuality, these nations desperately require significant investments. Exchange rate volatility is one of the many dangers foreign investors face. This volatility is an essential element that could restrict trading volume and reduce investment. Such fluctuations, which arise in industrialized nations, lead to instability on a worldwide scale. The present article studies the relationship between absolute exchange rate volatility and foreign direct investment (FDI). This study covers 13 developing countries over the period 1980–2022. The model used in this work is an Auto Regressive Distributed Lag (ARDL) to estimate the impact of the Real Exchange Rate and its Volatility on FDI. Our results indicate that the exchange rate volatility hurts FDI both in the short and long term. A positive relationship between FDI and REER has also been approved. The findings of this study suggest that developing countries must implement monetary policies to ensure a stable exchange rate that attracts more foreign direct investment. JEL Classification Codes: C130, F310, G150.